2022
DOI: 10.1093/brain/awac080
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ancestry GWAS reveals excitotoxicity associated with outcome after ischaemic stroke

Abstract: During the first hours after stroke onset neurological deficits can be highly unstable: some patients rapidly improve, while others deteriorate. This early neurological instability has a major impact on long-term outcome. Here, we aimed to determine the genetic architecture of early neurological instability measured by the difference between NIH stroke scale (NIHSS) within six hours of stroke onset and NIHSS at 24 h (ΔNIHSS). A total of 5,876 individuals from seven countries (Spain, Finland, Poland, United Sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Ancestry is a fixed characteristic of the genome. It influences the pathology and symptomatology of diseases by determining the genetic architecture [ 172 , 176 ]. NMs administered to subjects with different ancestral backgrounds may yield different results.…”
Section: Perspectivesmentioning
confidence: 99%
“…Ancestry is a fixed characteristic of the genome. It influences the pathology and symptomatology of diseases by determining the genetic architecture [ 172 , 176 ]. NMs administered to subjects with different ancestral backgrounds may yield different results.…”
Section: Perspectivesmentioning
confidence: 99%
“…The GWAS studies may allow us to uncover genes and pathways that shape the dynamic processes involved in stroke outcomes from early brain injury to long-term recovery. Despite the high number of genetic risk loci associated with stroke risk (>30 loci) [ 7 ], only a few have been associated with stroke outcome [ 21 , 22 , 23 ], thus suggesting that genetic factors related to stroke outcome are likely to be different from those influencing stroke risk. In addition, it has been observed that early neurological change after stroke measured using ΔNIHSS24 h (the difference between the NIHSS score at 24 h and the NIHSS score at baseline (less than 6 h from stroke onset)), has a different genetic architecture than the risk of IS [ 24 ].…”
Section: Genetics Of Stroke Outcomementioning
confidence: 99%
“…The GENISIS (Genetics of Early Instability After Ischaemic Stroke) study performed a GWAS with 5876 individuals to examine neurological evolution in the acute phase of stroke using ΔNIHSS24 h. This study showed that common genetic variants accounted for 8.7% of the variance in ΔNIHSS24 h. The authors identified eight genome-wide significant loci associated with ΔNIHSS24 h ( Figure 1 ) [ 23 ]. These results explained only 1.8% of the variance in ΔNIHSS24 h. However, they also found that excitotoxicity could play an important role in neurological deterioration after stroke.…”
Section: Genetics Of Stroke Outcomementioning
confidence: 99%
“…The change in National Institutes of Health Stroke Scale (NIHSS) during the first 24 h post stroke ( NIHSS 24h ) has been used as a measure of evolution of neurological deficits in the acute phase. A GWAS of NIHSS 24h has identified 7 genetic loci that harbor genes influencing excitotoxicity (Ibanez et al, 2022). Neuroimaging endophenotypes that capture hemorrhagic transformation or edema formation are also of great interest.…”
Section: Understanding Post-stroke Outcomes and Vcidmentioning
confidence: 99%